FALAH AS THE ULTIMATE GOAL IN SHARIA BANKING PERFORMANCE: BASED TO ISLAMIC ECONOMIC AXIOLOGY - Iqlima Azhar; Muhammad Salman; Nasrul Kahfi Lubis; Saparuddin; Yenni Samri Juliati Nasution (CV. RADJA PUBLIKA, 2025)
To achieve holistic prosperity (Falah), economics can be used to examine human behavior when faced with a dilemma. The Islamic economic system is founded on notions from the Qur'an and hadith, which give an economic order for achieving overall prosperity. To achieve this prosperity, Islamic commercial banks must be able to generate shareholder faith in the funds in which they invest; thus, it is vital to compare Sharia Banks' performance to their financial reports, which are based on Islamic values. This study examined the impact of BOPO (Operating Expenses and Operating Income) on Sharia Banking Performance, as measured by the Return On Assets (ROA) ratio, with FDR (Financing to Deposit Ratio) acting as a moderating variable. The research object is Bank Aceh Syariah using data analysis techniques used are financial reports published on the Bank Aceh Syariah website from 2016 to 2022. The test tool uses multiple linear regression tests and Moderate Regression Analysis (MRA) with SPSS. The research results show that BOPO has a significant effect on Sharia Banking Performance (ROA), but the FDR variable has not been able to moderate the relationship between BOPO and ROA.